Flagellar Morphogenesis: Protein Targeting and Assembly in the Paraflagellar Rod of Trypanosomes - Bastin, Philippe (American Society for Microbiology, 1999)
The paraflagellar rod (PFR) of the African trypanosome Trypanosoma brucei represents an excellent model to study flagellum assembly. The PFR is an intraflagellar structure present alongside the axoneme and is composed of two major proteins, PFRA and PFRC. By inducible expression of a functional epitope-tagged PFRA protein, we have been able to monitor PFR assembly in vivo. As T. brucei cells progress through their cell cycle, they possess both an old and a new flagellum. The induction of expression of tagged PFRA in trypanosomes growing a new flagellum provided an excellent marker of newly synthesized subunits. This procedure showed two different sites of addition: a major, polar site at the distal tip of the flagellum and a minor, nonpolar site along the length of the partially assembled PFR. Moreover, we have observed turnover of epitope-tagged PFRA in old flagella that takes place throughout the length of the PFR structure. Expression of truncated PFRA mutant proteins identified a sequence necessary for flagellum localization by import or binding. This sequence was not sufficient to confer full flagellum localization to a green fluorescent protein reporter. A second sequence, necessary for the addition of PFRA protein to the distal tip, was also identified. In the absence of this sequence, the mutant PFRA proteins were localized both in the cytosol and in the flagellum where they could still be added along the length of the PFR. This seven-amino-acid sequence is conserved in all PFRA and PFRC proteins and shows homology to a sequence in the flagellar dynein heavy chain of Chlamydomonas reinhardtii.